Anti-Theft Protection of Vehicle Using GPS Tracker & Android Apps - Sidiq Syamsul Hidayat; Karina Laras Novitasari; Amin Syarifuddin; Wilda Puspa Pratiwi; Sri Hardiningsih HS; Rev. Ariawan Pratomo (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The vehicle's anti-theft system is a module used to protect motor vehicles from theft by using three layers of security. The first layer uses a registered fingerprint for user authentication that can enable the machine on. The second one uses a GPS tracker to recognize where the position of the vehicle. The third one of security uses a remote engine cut-off system to shut down the machine remotely using the Android app. The system consists of two separate modules that are connected using a mobile data network. The first module is attached to the motorcycle body consists of fingerprints for biometric verification, GPS tracker for vehicle tracking and a microcontroller that controls the entire onboard system, including turning on and off the machine remotely. The second module is an application on the Android system used to detect where the location of the vehicle and applications that can be used to shut down the machine remotely. The method used in this research is the waterfall, it consists of systems and software design, module creation, module testing, module integration, system testing, operation and repair. The results shows this system is trusted to secure the motor vehicle by using a fingerprint as user authentication and GPS Tracker in which accurately detect the location of the motor vehicle, and then the system can shut down the motor power from a distance so that it can discover the theft of the vehicle. The conclusions: 1) The motorized vehicle safety system that is created to ease the owner of motor vehicle to control (On/Off) the vehicle remotely; 2) Si Kemot tool has been created to provide and increase the sense of security for vehicle owners because it can provide information on the position of the coordinates and speed of the vehicle; 3) the system can be controlled simply by using Android-based gadget that is very simple and ease of operation.